Adaptive Growth – Public Health and Medium for Global Health Development - Ravoopi, Rimasha Lahana (Caucasus Journal of Health Sciences and Public Health, 2020)
In the last few decades statistically the pace of technical development was of many fold, entering into robotic era it turns to make human race difficult health and developmental crisis. Principle aim of the research was to understand the problem understanding behind the diseases and symptoms in public healths services that pulls back the health of one individual (mental and physical health) in this robotic era. Even past research was taken into consideration on sleep disturbances during this SARS COVID 2, to understand the important of mental health and its prior analysis. State and national health ministry data in prior to health status a by researchers was taken in to analysis in the field of systemic diseases registered Death analysis in the past decade accordance to the scientific review .to understand the disturbances of sleep 208 males and 364 females who are university students are surveyed with few questions based on their sleep - wake pattern, sleep complaints, mood, alertness. They surgery understud and analysed 6 chronotypes left to their phone during covid: DIURNAL TYPE, they was no drastic disturbance seem from usual. We concluded that in 6 chronotypes morning wakers have better health conditions as said the mental health is good after 9 cycles of sleep and proper productive planning of day with awareness good bring better mental health results and development. Last epidemics were taken into consideration established the background of developed diseases infections and functionally disturbing which organ. The development was analysed Health and death statistics was analysed based on cardiovascular, nerurological, nephrologically and primarily cancer. We understud the disease of death was interlinked where the primary cause of death in many people was standing in linked comorbibity death of kidney and heart diseases. Common ICU treatment in cardiology was analysed to understand the contra indication and tolerance towards the drugs( RX: receptor blockers, placebo ( research )). It is clearly showed that medical treatment showed to be more of services with mistake of medical assistance or highly stimulated death (late on arrival). Communicate diseases were noted to understud that research ok basic antibiotics turned to be tough due to unprescribed usage of antibiotics , due to lack of awareness and illiteracy. The research articles concluded the public health by awareness in the areas of radiation, diet and sleep with analysis of future diseases saying it might be effecting thoat and brain mostly.